2017
DOI: 10.3389/fpls.2017.01533
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Regulation of GA Metabolism during Vernalization, Floral Bud Initiation and Development in Pak Choi (Brassica rapa ssp. chinensis Makino)

Abstract: Pak choi (Brassica rapa ssp. chinensis Makino) is a representative seed vernalization vegetable and premature bolting in spring can cause significant economic loss. Thus, it is critical to elucidate the mechanism of molecular regulation of vernalization and floral bud initiation to prevent premature bolting. Gibberellin (GA) is the key plant hormone involved in regulating plant development. To gain a better understanding of GA metabolism in pak choi, the content of GA in pak choi was measured at different stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 44 publications
2
14
0
2
Order By: Relevance
“…GA 1 , GA 4 , and GA 7 were detected at all stages of flower bud differentiation, while GA 3 was detected at pre-flower bud differentiation (Table 3). GA 1 and GA 4 were more sensitive to low overnight temperature than GA 7 , since GA 7 is not the subject of degradation by GA2 oxidases (Table 3) [29], and lower-temperature treatment can increase GAs content during floral bud differentiation, in agreement with a previous report [41].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…GA 1 , GA 4 , and GA 7 were detected at all stages of flower bud differentiation, while GA 3 was detected at pre-flower bud differentiation (Table 3). GA 1 and GA 4 were more sensitive to low overnight temperature than GA 7 , since GA 7 is not the subject of degradation by GA2 oxidases (Table 3) [29], and lower-temperature treatment can increase GAs content during floral bud differentiation, in agreement with a previous report [41].…”
Section: Discussionsupporting
confidence: 90%
“…GA metabolites show a strong temperature-dependent accumulation during flower bud differentiation in tomato (Figure 4; Table 3). By analyzing the expression profiles of GAs, the changes in the expression of SlGA2ox genes encoding degradation enzymes related to GA metabolism were downregulated significantly after lower-temperature treatment in agreement with a previous report [41]. In order to further elucidate the results of changes in the expression of SlGA2ox genes in tomato after lower overnight temperature treatment, the GA content in tomato was analyzed.…”
Section: Discussionsupporting
confidence: 86%
“…To analyze the effects of the exogenous addition of the hormone GA and the GA inhibitor PP 333 on endogenous hormones, the expression levels of key genes in the GA synthesis and signaling pathways were determined (Figure 1B). Three key genes in in the GA synthetic pathway, namely, ent-kaurene synthase ( KS ), ent-kaurene oxidase ( KO ), and ent-kaurenoic acid oxidase ( KAO ), and two typical genes in the GA signaling pathway, namely, DELLA and GA-insensitive drawf1 ( GID1 ), were selected [39]. Their analysis revealed that KS and GID1 gene expression showed a decreasing trend during floral bud differentiation, and no significant difference was obtained after the treatments.…”
Section: Resultsmentioning
confidence: 99%
“…In B. rapa , low-temperature treatment increases the GA content, and enhanced GA accumulation initiates floral bud differentiation [210]. Expression patterns of most genes involved in GA metabolism, particularly those of four genes including one GA20ox were consistent with observed GA levels [210].…”
Section: Conserved and Divergent Flowering Time Genes In Brassicacmentioning
confidence: 94%